Diaporthe and Diplodia Species Associated with Walnut (Juglans regia L.) in Hungarian Orchards - Andrea Zabiák; Csilla Kovács; Ferenc Takács; Károly Pál; Ferenc Peles; Erzsébet Fekete; Levente Karaffa; Kata Mihály; Michel Flipphi; Erzsébet Sándor (Horticulturae, 2023)
Walnut (Juglans regia L.) production is a developing sector in Hungarian horticulture, where preharvest fruit rot increasingly causes economic losses. Previously, fungi from the Diaporthaceae and Botryosphaeriaceae families were isolated with a high incidence from rotten fruits. Here, we identify these pathogens from different plant parts (twigs, buds, and shoots) in orchards in the north-east of Hungary, and test their pathogenicity on immature nuts. Diaporthe eres Nitschke and Diplodia seriata De Notaris were identified in isolates from different symptomatic and asymptomatic plant parts based on their ITS (nuclear ribosomal internal transcribed spacer) and tef1 (translation elongation factor EF-1-alpha gene) DNA sequences. Purified monocultures caused rot of immature nuts following in vitro inoculation. Our results suggest that D. eres Nitschke and D. seriata De Notaris lingering on buds and overwintering woody parts may affect the seasonal nuts through wound infection. Infection by Diaporthe and Botryosphaeriaceae species present on woody plant parts, as well as on/in buds has been reported in Mediterranean countries. This is the first report of such stepwise aetiology from a region with continental weather. Climate change, associated weather patterns and the limitations of fungicide use in the European Union, among other factors, could be responsible for the increasing number of infections and economic damage caused by these pathogens.